The Effect of Promotions Through Instagram Social Media on Purchase Decisions at the Shopee Marketplace - R. Misriah Ariyanis S; Vita Dhameria; Ersha Pratiwi (Jurnal Mantik, 2021)
This study was conducted to determine the magnitude of the influence of promotion through Instagram social media on purchasing decisions at the Shopee Marketplace (Study on Teenagers in Kesambi District, Cirebon City). The variables of this research are Promotion (X) as the independent variable and Purchase Decision (Y) as the dependent variable. Sampling using purposive sampling technique, namely the determination of the sample with certain considerations. There are sample criteria as follows: (1) Male and female respondents aged 10-24 years. (2) Respondents live in Kesambi District, Cirebon City (3) Respondents have seen Shopee advertising promotions on Instagram. The number of samples is 100 people. The data collection instrument used was a questionnaire/questionnaire distributed to the respondents. The research method used is associative quantitative method (relationship) with simple linear regression analysis while statistical testing is done by t test. The results of the correlation coefficient analysis show that there is a "Sufficiently High Relationship" and a coefficient of determination (R2) of 44% which is included in the category of "High Enough Influence". While the remaining 56% is influenced by other factors not examined. The results of hypothesis testing indicate that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This means that promotion through Instagram social media has a significant influence on purchasing decisions on the Shopee marketplace.